Distingsi Pemberdayaan Masyarakat Melalui ZISWAF dalam Meningkatkan Ekonomi Masyarakat - Fauzy Bahitsul, Ahmad; Karunia, Indah; Putri Pratiwi R, Helvira; Faizzatul Amalia, Nur (Management of Zakat and Waqf Journal (MAZAWA), 2021)
The purpose of this study is to find out in detail about ziswaf and find out the explanation and analyze the purpose of ziswaf in the community economy. Because it is very influential to find out how to improve the community's economy. If the empowerment in the community is good, it will realize the desired community economy. And vice versa, if community empowerment is not stable, social inequality will appear in society. People do not understand about zakat, infaq, shadaqoh, and waqf (ZISWAF), people assume that zakat fitrah and zakat maal in general, people cannot distinguish between income that has been affected by zakat or is still just infaq, and alms, and there is no grouping of benefit receipts. from the collection of zakat, infaq, shadaqoh, waqf funds (ZISWAF). The purpose of this implementation is oriented to community development, achieving the planned socialization program, increasing community capacity in the economic field, namely zakat, infaq, shadaqoh, waqf (ZISWAF). People's understanding increases about the true meaning of it. The implementation of this activity shows that there is an increase in public knowledge about the importance of zakat, imfaq, shodaqoh. And waqf (ZIZWAF) in improving the community's economy